Simultaneous cyclic deracemisation and stereoinversion of alcohols using orthogonal biocatalytic oxidation and reduction reactions. Issue 24 (28th October 2020) - Nafiu, Sodiq A.; Takahashi, Masateru; Takahashi, Etsuko; Hamdan, Samir M.; Musa, Musa M.
Abstract : We developed a concurrent cyclic deracemisation approach for secondary alcohols that combines a non-stereospecific oxidation step and a stereoselective reduction step using two mutants of Te SADH that exhibit various extents of stereoselectivities. Abstract : We developed a concurrent cyclic deracemisation approach for secondary alcohols that combines a non-stereospecific oxidation step and a stereoselective reduction step using two mutants of Thermoanaerobacter pseudoethanolicus secondary alcohol dehydrogenase ( Te SADH) that exhibit various extents of stereoselectivities. In this approach, W110G Te SADH, a sparingly stereoselective mutant, performs the non-stereospecific oxidation step and W110V/G198D Te SADH performs the stereoselective reduction step. The use of orthogonal cofactor regeneration systems allowed for the spontaneous operation of these mutants. ( S )-Configured alcohols were obtained in moderate ee's from their racemates using this strategy. To our knowledge, this report provides the first example of a fully enzymatic cyclic deracemisation with a stereoselective reduction step (CD-RS) for alcohols. This approach was further improved into a deracemisation strategy via stereoinversion using concurrent ( R )-selective I86A Te SADH-catalysed oxidation that leaves ( S )-alcohols untouched and W110V/G198D Te SADH-catalysed stereoselective reduction of the resultant ketone intermediates into the corresponding ( S )-configured alcohols. The latter strategy enabled quantitative production of ( S )-1-phenylethanol in >99% ee from its racemate. Overall, we show the superiority of the stereoinversion deracemisation approach for alcohols when compared with cyclic deracemisation, which is mainly due to the elimination of futile cycles in the former.